The Pakistan Expanded Program on Immunization and the National Immunization Support Project : An Economic Analysis - Haque, Minhaj Ul; Waheed, Muhammad; Masud, Tayyeb; Malick, Wasim Shahid; Yunus, Hammad; Rekhi, Rahul; Oelrichs, Robert; Kucheryavenko, Oleg (Washington, DC: World Bank, 2017)
Pakistan faces a formidable challenge in eliminating the polio virus from the country. With transmission of the polio virus substantially slowing in the Africa region, the only two countries worldwide with ongoing endemic polio transmission may soon be Pakistan and Afghanistan. A substantial number of the polio cases or infant paralysis occurring in Afghanistan is linked to cross-border transmission from Pakistan. The ongoing cycle of polio infection is not just a tragedy for the children of Pakistan, it is a global public health emergency constituting one of the final barriers to permanently eradicating polio. This paper demonstrates clear economic benefits and efficacy of the National Immunization Support Project (NISP), which is financing interventions in terms of DALYs saved, and establishes that this approach is affordable and economically effective with a high rate of return. In addition to increased investment, the effectiveness of the Expanded Program on Immunization can be enhanced by improving the capacity building of health professionals, as well as by improving logistics of program interventions to reach marginalized populations, remote areas, and pockets of resistance. An increased financial investment alone will be insufficient to address the root causes of persistent under-coverage of immunization in Pakistan. It is imperative that ample attention and resources be diverted to strengthen the procurement systems, local and provincial management capacity, and reporting mechanisms, among other capacity improvements.